GBS-1, a new medium for the isolation and culturing of Agrobacterium tumefaciens - Guiñez, J. R.; Bravo, A. R.; Salas, R. J. (Ciencia)
Culture media 1-A, recommended for the growth of memben of the genus Agrobacterium was modified. The resulting nutrient combination alowed isolation and abundant growth of a selected strain of Agrobacterium tumefaciens.